BENTUK DAN MAKNA GEBYOG ÉMPÉR RUMAH TRADISIONAL JAWA - Budiwiyanto, Joko (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2021)
The background of this research is that the Javanese house gebyog has a variety of shapes, is beautiful, but has almost the same pattern. The shape and size of the gebyog always follow the size of the Javanese house. The number of gebyog is always odd. However, not all Javanese houses use gebyog émpér. Only Javanese houses in rural areas with closed pendhapas have gebyog émpér. The relationship between the form of gebyog émpér and the spatial pattern of a traditional Javanese house in the meaning that is hidden behind its beauty is interesting. This study aims to determine the form and meaning of the Javanese house gebyog émpér. The research strategy uses qualitative. The research locations include the cities of Surakarta, Wonogiri, Sragen, Sukoharjo, Klaten, and Karanganyar. Sources of data extracted include informants and artifacts. Data collection techniques used in-depth interviews and observation techniques. The analysis technique uses interactive techniques. The results of the study are as follows, the pattern of gebyog forms is varied and symmetrical. Gebyog èmpèr controls the entrance from an unlimited free area to a restricted space due to possession and more.